Peer To Peer Lending : Hubungan Hukum Para Pihak Dan Perlindungan Hukum Apabila Gagal Bayar - Hugo Fernando Felix; Dewa Gede Pradnyana Yustiawan (International Forum of Researchers and Lecturers, 2023)
The aim of this publication is to clarify the legal relationship between parties involved in peer-to-peer lending as well as legal protection in the event of default. This research uses a method known as normative legal research or library law research, where secondary data or library materials are used as source material. In addition, this page explains in general the P2P lending model, rules, P2P lending arrangements in Indonesia, and consumer legal protection. Based on this research, it is known that the parties involved in P2P lending have power relations, loan agreements, and cooperation agreements. Depending on the cause of default, the lender or P2P Lending provider may be liable for default risk. Although illegal P2P lending is not subject to OJK regulations, legal P2P lending businesses are regulated by the Financial Services Authority (OJK) and must comply with OJK regulations. Subjective terms are violated by loan agreements signed through illegal P2P Lending, allowing requests for cancellation in court.